The method of multi-objective parametric design of magnetic field active canceling robust system for residential multy-story buildings closed to double-circuit overhead power lines - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V.; Voloshko, O. V.; Kolomiets, V. V.; Kobylianskyi, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Aim. Development the method of multi-objective parametric design for robust system of active canceling of magnetic field based on binary preference relations of local objective for multi-objective minimax optimization problem. Methodology. Spatial location coordinates of the compensating winding and the current in the shielding winding were determined during the preference-based multi-objective parametric design of systems of active canceling based on solution of the vector minimax optimization, in whith the vector objective function calculated based on Biot-Savart's law. The solution of this vector minimax optimization problem calculated based on nonlinear Archimedes algorithm. Components of Jacobi matrix and Hesse matrix calculated based on multi-swarm multi-agent optimization. Results. Theoretically and experimentally confirmed the effectiveness of reducing the level of the magnetic field in residential multy-storey old building of a doublecircuit overhead power transmission lines with a barrel-type arrangement of wires by means of active shielding with two compensation winding. Originality. The method of multi-objective parametric design for robust system of active canceling of magnetic field based on binary preference relations of local objective for multi-objective minimax optimization problem is developed. Practical value. It is shown the possibility to reduce the level of magnetic field in residential multy-storey old building closed to double-circuit overhead power transmission lines with a barrel-type arrangement of wires by means of system of active canceling with two canceling winding to a level safe for the population with an induction of 0.5 μT.

Мета. Розробка методу багатокритеріального параметричного проектування системи активного екранування на основі бінарних відносин переваги локальних критеріїв векторної мінімаксної оптимізації. Методологія. Просторові координати розташування компенсаційних обмоток та струми в цих обмотках визначали під час багатокритеріального параметричного проектування системи активного екранування на основі бінарних відносин переваги векторної мінімаксної оптимізації, в якій векторна цільова функція розрахована на основі закона Біо-Савара. Рішення цієї задачи векторної мінімаксної оптимізації розраховано на основі нелінійного алгоритму Архімеда. Елементи матриць Якобі та Гессе розраховано на основі багаторойної багатоагентної оптимізації. Результати. Теоретично та експериментально підтверджена ефективність зниження рівня магнітного поля в житлових багатоповерхових приміщеннях старої забудови дволанцюгових повітряних ліній електропередачі з бочкоподібним розташуванням проводів за допомогою активного екранування з двома компенсаційними обмотками. Оригінальність. Розроблено метод багатокритеріального параметричного проектування системи активного екранування на основі бінарних відносин переваги локальних критеріїв векторної мінімаксної оптимізації. Практична цінність. Показана можливість зниження рівня магнітного поля в житлових багатоповерхових приміщеннях старої забудови дволанцюгових повітряних ліній електропередачі з бочкоподібним розташуванням проводів за допомогою активного екранування з двома компенсаційними обмотками до безпечного для населення рівня з індуцією 0,5 μT.
Keywords: double-circuit overhead power transmission line; barrel-type arrangement of wires; magnetic field; system of active canceling; multi-objective parametric design; computer simulation; experimental research; дволанцюгова повітряна лінія електропередачі; бочкоподібне розташування проводів; магнітне поле; система активного екранування; багатокритеріальне параметричне проектування; комп'ютерне моделювання; експериментальні дослідження